Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 2004)
Table of Content Matthew Buckingham by Anselm Franke 20 Years of Parkett Essay by Boris Groys, 2 interviews with Alex Katz by Ena Swansea and Bruce Hainley Monica Bonvincini Monica Bonvincini’s Fetish Art by Juliane Rebentisch Crash Course in Architectural Matter by Lars Lerup Secrets of Sentence Building by Jörg Heiser Urs Fischer Postcard from America – Down the Rabbit-Hole in Zurich by Brenda Richardson Wanted to turn the music on but itw as already playing by Beatrix Ruf Garden of Earthly Hates by Benjamin Weissman Richard Prince A Reflection or Two by Dike Blair How I Learned to Stop Worrying and Love the Joke (Painting) by Douglas Fogle Richard Prince’s Second House by Alison M. Gingeras Richaard Prince – A Reader by Vincent Pécoil Loredana Sperini, Insert Wind and Fire Rising Within – Silvie Defraoui by Daniel Kurjakovic Variations on a Theme – Christina Jankowski by Marc Glöde Promise Pieces, Cumulus from America by Stephanie Smith Global Scrabble, Cumulus from Europe by Hans Rudolf Reust
It used to be a much-debated topic with a buzzword all its own: individual mythologies. The works of Monica Bonvicini, Alex Katz, Richard Prince, and Urs Fischer unmistakably demonstrate how fluid the exchange between collective and individual, between subculture, elitist culture and mainstream has become. But these artists also show that myths may be found and artistically enhanced in the most unexpected places. Also in this issue an Insert by Loredana Sperini. (editorial by publisher)
boek
Keywords: Bonvicini, Monica; Prince, Richard; Katz, Alex; Fischer, Urs